An affair to remember [videorecording (DVD)] - McCarey, Leo; Grant, Cary, 1904-1986; Kerr, Deborah, 1921-2007 (Twentieth Century Fox Home Entertainment, 2002)
Nickie Ferrante and Terry McKay meet on an ocean liner and fall deeply in love. Though each is engaged to someone else, they agree to meet six months later at the Empire State Building if they still feel the same way about each other. But a tragic accident prevents their rendezvous, and the lovers' future takes an emotional and uncertain turn.